(untitled) (Jurnal Destinasi Pariwisata, 2025)
The prohibition against entering temples during menstruation is often the subject of criticism in feminist discussions, as it is seen as discriminating against women for a natural biological experience. This study aims to identify the motivations of feminist tourists and analyze the implications of the prohibition on entering temples during menstruation on the satisfaction of feminist tourists when visiting the Uluwatu Temple Tourist Attraction. This study used a mixed-methods approach with quantitative data analysis through a 1–5 Likert scale to measure motivations and multiple linear regression analysis based on the Expectancy Disconfirmation Theory framework to assess satisfaction. Additionally, interactive data analysis further enriched the findings. The results indicate that feminist tourists’ motivations ranked from highest to lowest are curiosity (4,33), relaxation (4,27), self-empowerment (4,21), knowledge (4,19), and meaningful experience (4,14). Simultaneously, the variables of Expectation, Performance, and Disconfirmation have a significant effect on Satisfaction. Partially, Disconfirmation is proven to be the strongest and mediating variable (B = 0,456, sig. < 0,001), followed by Performance (B = 0,430, sig. < 0,001), while Expectation shows the weakest but still significant influence (B = 0,178, sig. = 0,016). Thus, although the menstruation prohibition contradicts certain feminist values, due to low initial expectations regarding the restriction, the fact that most tourists were not menstruating during the visit, and the non-repressive implementation of the rule, it ultimately had a neutral to relatively positive implication on tourist satisfaction. The study recommends improving pre-visit communication quality regarding local Balinese-Hindu culture and beliefs.